Pendampingan Kegiatan Pengembangan Modul Ajar Pembelajaran Matematika Berbasis Etnomatematika NGADHU BHAGA - Wewe, Melkior; Bela, Maria Editha; Bhoke, Wilibaldus; Wangge, Maria C.T (Civiliza Publishing, 2024)
The purpose of the community service activity is to improve the ability of mathematics teachers at the Junior High School level in South Golewa District to develop teaching modules based on Ethnomathematics, through mentoring activities for teachers to develop teaching modules, and to find out the teachers' responses to the activities carried out. This activity was carried out at SMPN Satap Golewa Selatan with 10 Mathematics Teachers who are members of MGMP in South Golewa District. The approach used in this activity is Interview, Face-to-face, and direct mentoring which was carried out in July 2024. The data collection instrument used in the Community Service activity was a participant response questionnaire in the Likert scale category on a 4-point scale, namely very good, good, less good, very less good. The data was analyzed referring to indicators, namely participant satisfaction, material relevance, and usefulness. The results of the mentoring activities showed that the satisfaction aspect showed a very good response, the relevance of the material was very good, and the usefulness of the material was very good.